2015
DOI: 10.1038/ncomms10166
|View full text |Cite
|
Sign up to set email alerts
|

Intestine-selective farnesoid X receptor inhibition improves obesity-related metabolic dysfunction

Abstract: The farnesoid X receptor (FXR) regulates bile acid, lipid and glucose metabolism. Here we show that treatment of mice with glycine-β-muricholic acid (Gly-MCA) inhibits FXR signalling exclusively in intestine, and improves metabolic parameters in mouse models of obesity. Gly-MCA is a selective high-affinity FXR inhibitor that can be administered orally and prevents, or reverses, high-fat diet-induced and genetic obesity, insulin resistance and hepatic steatosis in mice. The high-affinity FXR agonist GW4064 bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
418
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(444 citation statements)
references
References 57 publications
21
418
2
3
Order By: Relevance
“…Also, our data suggest that premature piglet tissues have the capacity to readily take up preformed DHA and EPA given parenterally, especially DHA uptake in the brain. Ceramide concentrations have been implicated in the development of obesity and NAFLD (47,48). It was therefore interesting to see the high concentration of ceramide in the IL emulsion and the lack of ceramide in OV.…”
Section: Discussionmentioning
confidence: 99%
“…Also, our data suggest that premature piglet tissues have the capacity to readily take up preformed DHA and EPA given parenterally, especially DHA uptake in the brain. Ceramide concentrations have been implicated in the development of obesity and NAFLD (47,48). It was therefore interesting to see the high concentration of ceramide in the IL emulsion and the lack of ceramide in OV.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the specific microbiota composition in HFD-fed Klb -/-mice is not the primary cause of their resistance to DIO. Nevertheless, further studies are warranted to elucidate whether the specific microbiota observed in Klb -/-mice can impact host energy partitioning via changes in short-chain fatty acid production (43,44) or intestinal BA signaling (41,45,46). Hepatosteatosis (nonalcoholic fatty liver, NAFL) is a classic complication of obesity.…”
Section: Tgr5mentioning
confidence: 99%
“…Furthermore, treatment with a gut-specific FXR agonist, fexaramine, reduces diet-induced increases in hepatic glucose production in mice, likely due to a robust increase in FGF 15 (Fang et al 2015). In contrast, some studies suggest that intestinal inhibition of FXR may in fact be beneficial via a reduction in intestinally derived ceramides , Jiang et al 2015, or via increased GLP-1 signalling (Trabelsi et al 2015), warranting further research into FXR agonism/antagonism for the treatment of diabetes. Interestingly, it has also been proposed that FXR-mediated metabolic improvements are due to alterations of the gut microbiota (Ryan et al 2014).…”
Section: Bile Acidsmentioning
confidence: 99%